(untitled) (International Journal of Management (IJM), 2024)
This paper compares the systemic practices of apartheid South Africa and Israeli occupation. The authors leverage the perceived similarities between Israeli policies in the Occupied Palestinian Territories and apartheid-era South Africa to foster global empathy for Gaza and Palestine. By synthesising the deeply reviewed literature, a list of the different forms of institutionalized oppression and segregation from both historical and contemporary examples is set in a table. The authors then examine the mechanisms and the consequences of the apartheid practices on affected populations and the possibility of extending this to Gaza. The study aims to understand the time framework that such apartheid practices would bring more international solidarity and empathetic commitment towards ending the Israeli occupation. Therefore, this work is meant to resonate through creating new sustained waves of social justice that would help to inspire solidarity among the oppressed population of Palestine and stop possible spreading such regime into Gaza. It also heralds the beginning of the end of the occupation regime, taking an analogy of the apartheid in South Africa previously.